2018
DOI: 10.28920/dhm48.1.40-44
|View full text |Cite
|
Sign up to set email alerts
|

Immersion pulmonary oedema in a healthy diver not exposed to cold or strenuous exercise

Abstract: In healthy divers, the occurrence of immersion pulmonary oedema (IPE) is commonly caused by contributory factors including strenuous exercise, cold water and negative-pressure breathing. Contrary to this established paradigm, this case reports on a 26-year-old, well-trained combat swimmer who succumbed to acute IPE during static immersion in temperate (21°C) water, while using a front-mounted counterlung rebreather. The incident occurred during repeated depth-controlled ascent practice at the French military d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The same group also described a special forces trainee aged 26 years who had IPE with a front-mounted counter-lung rebreather. 31 The authors demonstrated that when in a head up position in the water with the automatic diluent valve adjusted as the diver had done, he was breathing against a negative pressure.…”
Section: Negative Pressure Breathingmentioning
confidence: 99%
“…The same group also described a special forces trainee aged 26 years who had IPE with a front-mounted counter-lung rebreather. 31 The authors demonstrated that when in a head up position in the water with the automatic diluent valve adjusted as the diver had done, he was breathing against a negative pressure.…”
Section: Negative Pressure Breathingmentioning
confidence: 99%
“…We observed that after 30 min of controlled immersed exercising with identical dive-breathing devices, (i) the number of ultrasound lung comet tails was substantially higher in some subjects and (ii) the work of breathing was also markedly different between the subjects 16 . In addition, the number of lung comet tails, an indicator of the amount of extravascular lung fluid, correlated with the amount of work of breathing (WOB) and with markers of right heart congestion and of right/left ventricular imbalance 16 18 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the occurrence of symptoms of DCS and central oxygen toxicity CNSyn 13 , the inherent R risks considered related to:  incorrect composition of the breathing mix,  workload,  exposure to low temperature,  loss of oxygen supply,  increase in water surface roughness.…”
Section: Approachmentioning
confidence: 99%
“…French experience shows that the use of Nx-SCR CRABE SCUBA for MCM operations in shallow waters VSW may lead to the occurrence of pulmonary oedema accompanied by dyspnoea during the dive and later may lead to the appearance of fluid in the lungs or even death. This is due to the effect of negative pressure in the breathing space of the diving apparatus accompanying the expenditure of considerable effort and exposure to cold [12,13]. This may also be exacerbated by excessive hydration [14,15].…”
Section: Journal Of Polish Hyperbaric Medicine and Technology Societymentioning
confidence: 99%